THE EMERGENCE OF THE CLASSICAL ECONOMIC SCHOOL AND ITS EXPERIENCES - Samanov Abdurashid Andamovich (Web of Journals Publishing, 2025)
This article discusses the emergence of the classical economic school instead of mercantilism. The formation and consolidation of the classical school as a new method of production, as well as the history of the period when the history of the national economy and other social sciences were studied, it is explained what crafts, workshops and manufactures were, the absence of a clear division of labor in it, the emergence of capitalist relations are highlighted. In a different approach from the mercantilists, the representatives of the classical school studied the internal economic relations of capitalist relations that replaced feudalism.
Keywords: Mercantilism, classical economic school, history of the period, history of the national economy, social sciences, workshop, manufacture, handicraft, division of labor, capitalist relations.